O Corpo que dança : a arte de brincar - Santos, Dulce Olga Graças Leite de Oliveira (2011)
The research aims to present classic ballet as a creative way to develop playfulness by providing a development acquired by their own body experiences, aiding in their physical, mental and intellectual development. As an aid to the development of motor skills, it is believed that dance has the capacity to provide these children with a pedagogical as well as a psychological evolution, leading them to learn from their own body's free-acting experiences.